2015
DOI: 10.1016/j.homp.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Amphibians and ultra high diluted thyroxine – further experiments and re-analysis of data

Abstract: Although a perfect reproducibility was not obtained, this paradoxical phenomenon was generally consistent in different observations. Correlations were found between details of laboratory handling, as well as environment temperature, and the size of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
(34 reference statements)
3
17
0
1
Order By: Relevance
“…This finding was further scrutinized since, including histological research of an independent team, with the outcome of 9 comparable, 2 zero, and 0 opposite new results. 4,6 A study on animals from lowland biotopes and thyroxine 30Â added to the basin water had already shown not to be promising 1 in 1994 and had therefore not been pursued further.…”
Section: Part 1 (Biology)mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was further scrutinized since, including histological research of an independent team, with the outcome of 9 comparable, 2 zero, and 0 opposite new results. 4,6 A study on animals from lowland biotopes and thyroxine 30Â added to the basin water had already shown not to be promising 1 in 1994 and had therefore not been pursued further.…”
Section: Part 1 (Biology)mentioning
confidence: 99%
“…(However, the study yielding the zero result involved a greater number of animals than those yielding comparable results). 4,6 A multicentre study on thyroxine 30Â on the climbing activity of juvenile frogs that had reported a decrease in activity, 1 although promising, 4 was not pursued further due to ethical considerations.…”
Section: Part 1 (Biology)mentioning
confidence: 99%
“…Hormetic responses to stressors by amphibians appear in some studies (Wijesinghe 2012;James and Little 2003;Perez-Coll et al 2008) but not others (Miyachi et al 2002;Urine et al 2004;Endler et al 2015). Considering the known interactions between food intake, growth, and stress/immune responses in other organisms (especially homeotherms), we asked if immunochallenge of an immature ectherm, the Green Tree Frog (Hyla cinerea), might also draw resources from growth to fuel immunity.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous attempts have been made to study the physicochemical properties and standardization of UHDs beyond Avogadro's limit. [3][4][5][6][7][8][9][10][11][12] However, studies on the stability aspects of homeopathic UHDs remain limited. Lenger et al reported detection of photons in highly potentized homeopathic medicines by delayed luminescence, where the stability of sucrose globules was found to be better than ethanolic solutions.…”
Section: Introductionmentioning
confidence: 99%